Analisis Yuridis Pengesahan Perkawinan Beda Agama: Kajian Putusan Pengadilan Negeri Jakarta Pusat Nomor 155/Pdt.P/2023/PN.Jkt.Pst - Amira Shiba; Aulia Tiara; Kinanti Lukman (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the Decision of the Central Jakarta District Court Number 155/Pdt.P/2023/PN.Jkt.Pst concerning a petition for the legalization of an interfaith marriage between an Indonesian Muslim woman and an Indonesian Protestant Christian man, who solemnized their marriage in a church. The study focuses on four main aspects: (1) the reasons of the parties for entering into an interfaith marriage; (2) the legal standing of each party under both religious law and national law; (3) legal implications for the inheritance rights of children born from the interfaith marriage; and (4) the judge's considerations in granting legalization. Using a normative juridical method with case and statute approaches, the study finds that the judge's decision to grant legalization constitutes a progressive legal breakthrough placing individual civil rights and the best interests of the child above religious law differences, albeit creating normative tension with Article 2(1) of Marriage Law No. 1 of 1974.